DETERMINANTS FOR TOURISM AND POVERTY ALLEVIATION - SUSANA LIMA; CELESTE EUSÉBIO; MARIA DO ROSÁRIO PARTIDÁRIO (Tourism & Management Studies, 2011)
In the last decade, commitment to tourism as a development strategy for the developing world has gained a renewed interest by governments and development organizations in the fulfillment of the Millennium Development Goals. This was established as a major priority by donors, governments, NGOs, national and international tourism bodies, bilateral and multilateral institutions, like the United Nations World Tourism Organization (UNWTO). The purpose of this paper is to identify the main determinants that should be integrated in the international cooperation for development programs that use tourism as a tool for poverty alleviation. By way of a case study it is analyzed the role played by the UNWTO.Volunteers Program in this context examining if it integrates the determinants previously identified in the literature review. To accomplish the research objectives, data collection included: documental analysis, participant observation, and semi-structured interviews with UNWTO participants. While no evidences exist yet due to the recent implementation of the UNWTO.Volunteers, the findings suggest that if these programs manage to have a positive influence on all, or at least in some of the dimensions, then it is possible that it responds to some of the main determinants for poverty alleviation in order to reinforce the local communities capacity-building.